2007
DOI: 10.1016/j.jpsychires.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric morbidity and psychological adaptation of the nurses in a structured SARS caring unit during outbreak: A prospective and periodic assessment study in Taiwan

Abstract: To assess the rapidly changing psychological status of nurses during the acute phase of the 2003 SARS outbreak, we conducted a prospective and periodic evaluation of psychiatric morbidity and psychological adaptation among nurses in SARS units and non-SARS units. Nurse participants were from two SARS units (regular SARS [N=44] and SARS ICU [N=26]) and two non-SARS units (Neurology [N=15] and CCU [N=17]). Participants periodically self-evaluated their depression, anxiety, post-traumatic stress symptoms, sleep d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
453
12
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(548 citation statements)
references
References 29 publications
69
453
12
14
Order By: Relevance
“…Finally, 11 studies reporting on the relationship between critical incidents and post-traumatic stress symptoms (Ntotal ¼ 3866; range of N ¼ 92e934; Fig. 1) were considered eligible for inclusion (Chan & Huak, 2004;Chen, Wu, Yang, & Yen, 2005;Kerasiotis & Motta, 2004;Lin et al, 2007;Luce, Firth-Cozens, Midgley, & Burges, 2002;Maunder, Lancee, Balderson, Bennett, Borgundvaag, Evans et al, 2006;McAlonan, Lee, Cheung, Cheung, Tsang, Sham et al, 2007;Mealer, Shelton, Berg, Rothbaum, & Moss, 2007;Styra et al, 2008;Su, Lien, Yang, Su, Wang, Tsai et al, 2007;Weiniger et al, 2006); 6 of these studies (Ntotal ¼ 1695) also reported on the secondary outcomes, anxiety and depression (Chan & Huak, 2004;Chen et al, 2005;Kerasiotis & Motta, 2004;McAlonan et al, 2007;Mealer et al, 2007;Su et al, 2007).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 11 studies reporting on the relationship between critical incidents and post-traumatic stress symptoms (Ntotal ¼ 3866; range of N ¼ 92e934; Fig. 1) were considered eligible for inclusion (Chan & Huak, 2004;Chen, Wu, Yang, & Yen, 2005;Kerasiotis & Motta, 2004;Lin et al, 2007;Luce, Firth-Cozens, Midgley, & Burges, 2002;Maunder, Lancee, Balderson, Bennett, Borgundvaag, Evans et al, 2006;McAlonan, Lee, Cheung, Cheung, Tsang, Sham et al, 2007;Mealer, Shelton, Berg, Rothbaum, & Moss, 2007;Styra et al, 2008;Su, Lien, Yang, Su, Wang, Tsai et al, 2007;Weiniger et al, 2006); 6 of these studies (Ntotal ¼ 1695) also reported on the secondary outcomes, anxiety and depression (Chan & Huak, 2004;Chen et al, 2005;Kerasiotis & Motta, 2004;McAlonan et al, 2007;Mealer et al, 2007;Su et al, 2007).…”
Section: Search Resultsmentioning
confidence: 99%
“…In one study (Lin et al, 2007), SE was converted by the authors into SD (SD ¼ SE Â ON). In six other studies (Chan & Huak, 2004;Chen et al, 2005;Kerasiotis & Motta, 2004;Luce et al, 2002;Styra et al, 2008;Su et al, 2007), M(SD) of high-risk participants or low-risk controls that represented equivalent groups with respect to exposure to critical incidents were pooled according to the following formulas (where M p denotes pooled mean and SD p denotes pooled standard deviation):…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The SDS is a widely used multidimensional assessment scale in Chinese communities (25). It consists of four questions that measure four domains of role impairments, including work, home management, social life, and close relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Alta exposição a eventos traumáticos no trabalho foi associada ao desfecho, sendo consistente (Slottje et al, 2008;Su et al, 2007;van der Velden et al, 2006). Provavelmente, a natureza das atividades desempenhadas pelos bombeiros influencie negativamente a saúde mental, independente de outros estressores ocupacionais (Lima & Assunção, 2011).…”
Section: Eventos Extralaboraisadversos E Casos Prováveis De Tept Em Bunclassified